Effects of Eight Weeks of Cardiac Rehabilitation Training on Serum Levels of Sirtuin1 and Functional Capacity of Post- Coronary Artery Bypass Grafting Patients - Alsabah Alavizadeh, Nagmeh; Rashidlamir, Amir; Hejazi, Seyed Mahmud (Medical laboratory journal, 2019)
ABSTRACT              Background and Objectives: Cardiac rehabilitation improves functional capacity of post-coronary artery bypass grafting (CABG) patients. Therefore, the aim of this study was to evaluate effects of eight weeks of cardiac rehabilitation on serum levels of sirutin1 (SIRT1) and functional capacity of post-CABG patients.              Methods: Forty-five non-active men (mean age: 47.4 ± 3.3 years, duration of disease: 150 ± 69.12 months) were randomly divided into three equal groups: aerobic exercise, combined (resistance and aerobic) exercise and control. The subjects performed trainings at 60-75% of maximum heart rate, three sessions a week for eight weeks. Blood samples were collected 24 hours before the first exercise session and 48 hours after the last exercise session. Data were analyzed with SPSS 16.0 using one-way ANOVA and the Tukey post hoc test. P-values less than 0.05 were considered statistically significant.              Results: Aerobic and combined exercise increased serum SIRT1 levels and functional capacity. There was no significant decrease in body mass index (P=0.06). The SIRT1 level did not differ significantly between the two exercise groups after the intervention (P=0.91). There were significant difference between the study groups in terms of the travelled distance (P<0.034).              Conclusion: Both combined and aerobic exercise can increase serum levels of SIRT1, reduce body mass index and improve functional capacity in CABG patients.              Keywords: Resistance training, exercise, SIRT1.